Ngariung Bagja: Peningkatan Motivasi Belajar, Kreativitas, dan Kepedulian terhadap Lingkungan untuk Anak Usia Sekolah Dasar (Kasus Kampung Cikadu, Desa Rabak, Kabupaten Bogor) - Ahmad Aulia Arsyad; Efri Dwi Prabowo; Reza Salsa Febriana (Institut Pertanian Bogor, 2022)
The education sector is one of the sectors most affected by the COVID-19 pandemic. The policies set by the government as an effort to prevent the transmission of the Covid-19 virus have forced face-to-face learning activities to be temporarily suspended or carried out online. However, online learning certainly requires students and educators to have good devices and internet network access. In an effort to increase children's learning motivation, make them more open and able to express creativity through fun learning, a non-formal education program called Ngariung Bagja was compiled. The Ngariung Bagja program was implemented in Cikadu Sub-Village, Rabak Village, Bogor District, with the exact location at SDN Rabak 02. Based on the activities in the Ngariung Bagja program, a number of 12 children aged 9‒12 years experienced increased motivation to read, write, and tell stories. In addition, they can express creativity and art according to their respective interests and talents in the creation stage and produce plastic goods creations as a form of concern for the environment.